2020
DOI: 10.3389/fevo.2020.590281
|View full text |Cite
|
Sign up to set email alerts
|

Grooming Behavior in Naturally Varroa-Resistant Apis mellifera Colonies From North-Central Argentina

Abstract: Varroa-Resistance in Argentinian Honey Bees selection. Percentage of damaged mites appears to be a reliable measure to enhance this behavior in honey bee colonies by selective breeding. Finally, the importance of improving and protecting locally adapted honey bee populations with natural Varroa resistance for regional apiculture is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 91 publications
0
11
0
2
Order By: Relevance
“…Previous research on grooming behavior and damaged mites in Apis has shown that grooming behavior is a selected trait in naturally mite-resistant colonies (Peng et al, 1987;Boecking and Ritter, 1993;Fries et al, 1996;Arechavaleta-Velasco and Guzmán-Novoa, 2001;Russo et al, 2020). The mite-biting or grooming behavior of honey bees, as a defensive behavior against parasitic Varroa mites, can be used as a parameter to select for Varroa mite resistance in honey bee stocks (Spivak, 1996;Rinderer et al, 2010;Hunt et al, 2016;Pritchard, 2016;Morfin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on grooming behavior and damaged mites in Apis has shown that grooming behavior is a selected trait in naturally mite-resistant colonies (Peng et al, 1987;Boecking and Ritter, 1993;Fries et al, 1996;Arechavaleta-Velasco and Guzmán-Novoa, 2001;Russo et al, 2020). The mite-biting or grooming behavior of honey bees, as a defensive behavior against parasitic Varroa mites, can be used as a parameter to select for Varroa mite resistance in honey bee stocks (Spivak, 1996;Rinderer et al, 2010;Hunt et al, 2016;Pritchard, 2016;Morfin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Masaquiza et al (2017) estudiando colonias de abejas africanizadas en Ecuador, encontraron porcentajes de remoción de cría del 76% utilizando el método de pinchado con aguja, método que sobre-estima el comportamiento higiénico de las abejas (Espinosa-Montaño et al, 2008). Por lo anterior, puede concluirse que los resultados encontrados en este trabajo son importantes debido a que la potencial reproducción de genotipos de abejas con alto comportamiento higiénico, contribuye a aumentar la resistencia de las colonias a enfermedades (Guzman-Novoa y Morfin, 2019), lo cual es útil para reducir el uso de antibióticos en la prevención y tratamiento de brotes de enfermedades de la cría; asimismo, las colonias higiénicas tendrían menor cantidad de ácaros de V. destructor que aquellas no seleccionadas (Spivak, 1996) y pudieran ser capaces de mantenerse saludables a pesar de la existencia de colonias infestadas en el mismo apiario (Russo et al, 2020). Adicionalmente a la resistencia a enfermedades y ácaros parasitarios, el comportamiento higiénico de las abejas también ha sido relacionado con un efecto positivo en la producción de miel (Wielewski et al, 2012;Medina-Flores et al, 2014c).…”
Section: Discussionunclassified
“…Many variables influence V. destructor population growth, including climatic factors and genetic factors of the mites and host bees [34][35][36][37][38][39][40][41]. Additionally, infestation rates and V. destructor population growth are affected by reinfestation from drifting bees [42,43].…”
Section: Discussionmentioning
confidence: 99%